The Influence of Playdough Media on the Achievement of Cognitive Development of Children Aged 4-5 Years in TK Negeri 2 Pembina Medan - Dwi Purwanti; Anita Yus (Asian Journal of Applied Education (AJAE), 2023)
In this study, the problem is the achievement of children's cognitive development that has not fully developed significantly. This study aims to determine the effect of playdough media on cognitive development achievements of children aged 4-5 years at TK Negeri 2 Pembina Medan. This study uses an approach with experimental research methods (Quasi-experiment Design) with The Equaivalent Time Samples design. The population in this study were all children aged 4-5 years in class A with a total sample of 21 children at TK Negeri 2 Pembina Medan. The research was conducted with 3 treatments. The data collection instrument utilizes observation sheets. From the results of data analysis, the average score for treatment 1 was 5.85, then treatment 2 received a value of 7.85 while treatment 3 had an average value of 10.9. Based on data analysis through non-parametric hypothesis testing, the SPSS 26 statistic test value is 0.000. Therefore it can be concluded that playdough media has a significant influence on the achievement of cognitive development of children aged 4-5 years in TK Negeri 2 Pembina Medan.